2022
DOI: 10.1001/jamanetworkopen.2022.7559
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Atherosclerosis, Microalbuminuria, and Estimated 10-Year Atherosclerotic Cardiovascular Disease Risk in Sub-Saharan Africa

Abstract: Key Points Question Are novel cardiovascular disease (CVD) risk factors, such as carotid atherosclerosis (carotid intima-media thickness) and microalbuminuria, associated with with 10-year atherosclerotic CVD (ASCVD) risk in sub-Saharan African adults free of established CVD? Findings In this cross-sectional study of 9010 adult participants, microalbuminuria measured using spot urine albuminuria was associated with both carotid atherosclerosis and a high 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The underlying mechanisms underlying the associations between albuminuria and CVD risk are not well established. However, abnormal albuminuria indicates generalized vascular dysfunction and is related to systemic and coronary atherosclerosis [ 25 , 26 ]. In patients with T2D, increased uACR are likely an early signal of microvascular disease and indicate some degree of kidney damage [ 27 ].the widespread vascular disorder may progress to loss of vessel distension and generalized elevation of arterial blood pressure, ultimately predispose patients to the development of micro- and macrovascular disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms underlying the associations between albuminuria and CVD risk are not well established. However, abnormal albuminuria indicates generalized vascular dysfunction and is related to systemic and coronary atherosclerosis [ 25 , 26 ]. In patients with T2D, increased uACR are likely an early signal of microvascular disease and indicate some degree of kidney damage [ 27 ].the widespread vascular disorder may progress to loss of vessel distension and generalized elevation of arterial blood pressure, ultimately predispose patients to the development of micro- and macrovascular disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsushita et al 12 analyzed 637 315 individuals without a history of CVD from 24 cohorts and found similar results. Further, even microalbuminuria may indicate a high CVD risk 13 . In the 2012 Kidney Disease Improving Global Outcomes guidelines, eGFR and urinary protein were also included as criteria for classifying CKD stages.…”
Section: Discussionmentioning
confidence: 99%
“…Further, even microalbuminuria may indicate a high CVD risk. 13 In the 2012 Kidney Disease Improving Global Outcomes guidelines, eGFR and urinary protein were also included as criteria for classifying CKD stages. However, few studies have investigated the interactions between these two variables or combined them as a composite variable.…”
Section: Discussionmentioning
confidence: 99%
“…Common Carotid intema media thickness(CIMT) is measured by Using a B mode ultrasound with 7.5-10 MHz linear phased transducer with the patients lying supine and their neck extended and turned away from the side being examined [10] .…”
Section: Methodsmentioning
confidence: 99%